The Influence of Workload on Employee Performance with Teamwork as an Intervening Variable at the General Election Commission of Tanjung Jabung Timur Regency - Rahmadhaniati, Sustianda; Sumarni, Sumarni; Chairunnisa, Fitri (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to determine the influence of workload on employee performance with teamwork as an intervening variable at the General Election Commission of Tanjung Jabung Timur Regency. The analysis method used is quantitative analysis met hod. The population and sample are employees of the General Election Commission of Tanjung Jabung Timur Regency with a sample size of 30 employees. Data collection was carried out by distributing questionnaires with a Likert scale. The statistical analysis used is using the Structural Equation Modeling (SEM) technique, with Partial Least Square (PLS) as a processing tool using the SmartPLS program. The results of this study indicate that workload has a positive and significant effect on employee performance, workload has a positive and significant effect on teamwork, teamwork has a positive and significant effect on employee performance and workload has a positive and significant effect on employee performance mediated by teamwork. So it can be concluded that teamwork serves as a link between workload and employee performance.